Vulnerability analysis toward river flooding in the Comal Watershed, Indonesia - Wibowo Yunus Aris (EDP Sciences, 2021)
River flooding is a disaster that almost every year hits the downstream Comal watershed. This incident resulted in material, psychological, and even casualties. Therefore, a vulnerability analysis is needed to reduce the impact of flooding. This study aims to analyze the vulnerability to river flooding in the downstream Comal Watershed area, Indonesia. Vulnerability variables used are social, economic, physical, and ecological (environmental) vulnerability following the Indonesian National Disaster Management Agency (BNPB) Regulation 2012. Data were obtained from government agencies and interpretation of SPOT 5 satellite imagery. Data analysis were carried out using scoring and weighting. Moreover, the data classification were using the mean and standard deviation equations. The analysis showed that the vulnerability to river flooding in the Comal watershed area was dominated by a moderate vulnerable class of 10,832.15 hectares (49.69%) and distributed in 26 villages. Furthermore, the high level of vulnerability also covered a large area by 8,773.11 hectares (40.24%), and distributed across 29 villages. Therefore, proper river flooding mitigation planning with the characteristics of the area is needed.